Blended learning research: Identifying research output patterns in Scopus (2000-2023) - Ayala, Abrahán Cesar Neri; Valenzuela Narváez, Daniel Alberto Oswaldo; Manes Cangana, Gabriel Alberto; Orbe, Sergio La Cruz; Torres Anaya, Alexander Jorge; Ayala Huaynatte, Ender (Iberoamerican Journal of Science Measurement and Communication, 2024)
Objective. This study aims to analyze the bibliometric data on blended learning from 2000 to 2023 in Scopus. Methodology. This study was designed from a bibliometric perspective using Scopus as a data source. Frequency counts determined the productivity of authors, affiliations, and countries. The co-occurrence of terms was investigated using the author's keywords. Co-authorship and country collaboration networks were also constructed. Results. 949 authors with at least two publications were identified, 198 with three, 80 with four, 44 with five, and the remaining with more than six. About the co-authorship network, 1,223 authors were included in the map, and only 23 are connected. North America, Europe, and Asia have the highest productivity levels. The emergence of countries such as Indonesia and Malaysia indicated a growing interest in research on the topic addressed here. China and the United States have the strongest relationships. Clustering revealed thematic diversity and current relevance, an emphasis on personalization and accessibility of learning, growing interest in self-efficacy and autonomy, integration of new technologies, the importance of active learning and activity theory, and a focus on adult education. Conclusion. The field of blended learning lacks extensive collaborative networks. Author communities were notable for autonomy and segregation. The country's productivity data highlighted the necessity of sustained investment in research and development. Emerging nations demonstrated promising growth, while efforts to enhance research capabilities in lower-productivity countries could contribute to a more balanced global research landscape.